Opinions and Treatment Decisions for Dental Erosive Wear: A Questionnaire Survey among Icelandic Dentists - Aida Mulic; Inga B. Árnadòttir; Torbjòrg Jensdottir; Simen E. Kopperud (International Journal of Dentistry)
Dental erosive wear (DEW) is common among children and adolescents, and a survey of Icelandic children showed that 30.7% of 15-year-olds were diagnosed with the condition. Objective. To gain knowledge about dental practitioners’ experiences, opinions, and treatment decisions. Materials and Methods. A precoded questionnaire, previously used among Norwegian dentists, was sent electronically to all dentists in Iceland (n = 341). Results. The response rate was 64.2%, and 58% of dentists were male. More than half of the clinicians (54%) thought that prevalence had increased the last 10–15 years, and 67% reported it to be more common in male. Most (96%) recorded presence of DEW, but only 4% used a detailed scoring system. Lesions were mostly on occlusal surfaces of first mandibular molars (73%), on palatal in upper anterior teeth (61%), and on occlusal of maxillary first molars (36%). Most dentists (74%) reported a probable cause, e.g., high consumption of carbonated beverages (98%), acidic juices (68%), sport drinks (58%), reflux (54%), and eating disorders (20%). Dietary history was often recorded by 38%, and 65% never measured saliva. Most of the dentists (88%) treated patients themselves, and half of them preferred prevention with high fluoride and resin sealants. While some dentists wanted to restore teeth more invasively, most considered to restore with a filling. Conclusion. Icelandic dentists seem to be well educated for diagnosis and treatment of dental erosion, and dentists are aware of a minimally invasive approach. Clinical Significance. It is challenging for dentists to make the best treatment decision for patients with DEW, both in a short perspective and long perspective. At present, little is known about their knowledge and treatment approach, and there is no standard treatment which can be recommended. Therefore, the present study investigated dental practitioners’ treatment decisions, as well as knowledge, experiences, and awareness of DEW.